Navigating the Nexus of English Education and Artificial Intelligence: Opportunities and Challenges: English - Rizky Hidayatullah (Prodi Tadris Bahasa Inggris, 2023)
Education integration with Artificial Intelligence (AI) has brought to transformative change. The issue of Artificial Intelligence (AI) technology in the field of education, as discussed by various researchers this study delves into the intricate interplay between English education and AI. A mixed-methods approach was used to investigate the relationship between English education and AI. The research design included both qualitative and quantitative methodologies. The research instrument utilized a questionnaire distributed to 30 participants. These participants comprised students from the English Language program, English Language faculty members, and an AI specialist from the Doctor of Education Technology department. incorporating AI technology into English language learning provides several benefits, including faster and more efficient learning, a broader understanding, and the ability to know more. Students report that the most significant benefit of using AI technology for English learning is that it makes learning easier and more efficient. However, there are some drawbacks to using AI technology in English language learning, such as signal strength or slow Wi-Fi, the fear of humans becoming dependent on AI, and the need for more advanced technology.